2014
DOI: 10.4103/0300-1652.132068
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and presentation of acute abdomen in a Nigerian teaching hospital

Abstract: Background:Abdominal pain of sudden onset is the hallmark of most non-traumatic emergency surgical presentations. This presents a scenario of urgency to the young surgeon who has to determine which of a myriad of disease conditions the patient is presenting with. Such a physician has to rely on experience and a sound knowledge of the local aetiological spectrum in making a clinical diagnosis.Objective:To determine the epidemiology and aetiological spectrum of diseases presenting as acute abdomen in the adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 8 publications
(15 reference statements)
1
20
3
4
Order By: Relevance
“…In a study done by Yeboah O et al, the common cause of nontraumatic acute abdomen is acute appendicitis (22.4%) followed by perforation peritonitis (16.2%) and study done by Agboola et al, the commonest cause of nontraumatic acute abdomen is acute appendicitis (30.3%) followed by intestinal obstruction (27.9%). 5,11 Hence, findings in our study regarding spectrum of disease is different as compared with other two studies.…”
Section: Spectrum Of Diseasecontrasting
confidence: 53%
“…In a study done by Yeboah O et al, the common cause of nontraumatic acute abdomen is acute appendicitis (22.4%) followed by perforation peritonitis (16.2%) and study done by Agboola et al, the commonest cause of nontraumatic acute abdomen is acute appendicitis (30.3%) followed by intestinal obstruction (27.9%). 5,11 Hence, findings in our study regarding spectrum of disease is different as compared with other two studies.…”
Section: Spectrum Of Diseasecontrasting
confidence: 53%
“…Patients may present with vague complaints and varying associated symptoms making diagnosis difficult which ranges from benign to life-threatening conditions. 4 Abdominal pain can be the manifestation of a spectrum of disease processes. Conditions causing acute abdominal pain may vary, from conditions needing immediate intervention, to relatively mild presentations needing careful observation to avoid over investigation and unnecessary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Back home, Jain and Gupta in their study reported vomiting (72%), abdominal distension (50%), constipation (48%) and fever (41.8%) as the major findings in their study. 3,15 In general, vomiting, constipation and fever seem to be the major findings, however, their prevalence varies slightly in different studies which might be owing to difference in underlying etiology and profile of patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, majority of the studies, except those that included only female patients had a skewed gender ratio showing a high prevalence of males as compared to females. 3,[11][12][13][14][15] In the present study, major presenting symptoms except abdominal pain were fever (46.7%), constipation (42.86%) and vomiting (40.66%) respectively. In a study from Nigeria, Agboola et al, reported vomiting (68.5%), anorexia (56.9%) and fever (47.8%) as the major associated complaints apart from acute abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation